Hubungan Paparan Informasi Kesehatan Gigi Di Media Sosial Dengan Sikap Pemeliharaan Kesehatan Gigi Pada Mahasiswa Terapis Gigi Dan Mulut (Window of Public Health Journal, 2026)
Social media has become one of the primary sources of oral health information due to its accessibility and widespread use among young adults, including dental therapy students. Exposure to oral health information through social media may influence attitudes toward oral health maintenance; however, its effectiveness among future oral health professionals remains unclear. This study aimed to analyze the relationship between exposure to oral health information on social media and attitudes toward oral health maintenance among Dental Therapy students. A quantitative study with a cross-sectional design was conducted involving 60 Dental Therapy students selected using a total sampling technique. Data were collected using validated and reliable questionnaires measuring exposure to oral health information on social media and attitudes toward oral health maintenance. Data were analyzed using descriptive statistics and the Chi-square test with a significance level of 5%. Most respondents had a high level of exposure to oral health information on social media (71.7%) and demonstrated good attitudes toward oral health maintenance (76.7%). The Chi-square analysis revealed no statistically significant relationship between exposure to oral health information on social media and attitudes toward oral health maintenance among Dental Therapy students (p=0.067). Exposure to oral health information on social media was not significantly associated with attitudes toward oral health maintenance among Dental Therapy students. The findings suggest that students' attitudes may be influenced more by formal education, academic experiences, and the educational environment than by social media exposure alone. Social media should continue to be utilized as a complementary educational platform by providing evidence-based and credible oral health information.